METAMORFOSA PARANOIA DAN MOMEN KEPEMIMPINAN MENURUT ELIAS CANETTI - Aur, Alexander (STKIP Santu Paulus Ruteng, 2015)
Abstract: Paranoia Metamorphic and Moments of Leadership According to Elias Canetti. Leader with all his ability to lead often clash with those they lead. People are led at any moment can criticize and overthrow the leader. In the collision situation, the leader with all the authority and capacity, can be devastating-bullion those he leads, by means of terrorizing and killing. If there is such a leader, in fact he suffered from paranoia or fear of the